REKAYASA RAINWATER HARVESTING PADA SISTEM IRIGASI TETES DI GREENHOUSE SEBAGAI SOLUSI GAGAL PANEN AKIBAT KEKERINGAN DI KECAMATAN NITA - Kaidu, Triapriono; Lete, Maria Kurniaty; Ariyandi, Arnoldus Y. (Jurnal Teknik Sipil dan Arsitektur, 2026)
Nita Subdistrict, Sikka Regency, is a dry tropical region highly vulnerable to prolonged droughts that frequently cause crop failures in horticultural commodities. This study aims to analyze the potential of rainwater harvesting (RWH), estimate crop water requirements, and desing an integrated RWH system with drip irrigation ini greenhouses as an adaptive solution to limited water resources. Ten years of climatological data (2015-2024) were obtained from the meteorology, climatology, and geophysics angency (BMKG) and analyzed using the arithmetic mean, thiessen polygon, and isohyet methods. The analysis indicated that the isohyet method produced the most representative annual rainfall value of 2.080 mm. with a greenhouse roof of 102,01 m2 and a runoff coefficient of 0,8, the theoretical rainwater harvesting potential reached 169,75 m3 per year. Meanwhile, crop water requirements for tomato, long bean, chili, eggplant, cucumber, mustard greens, and water spinach were caculated using the FAO Penman-Monteith method with an average reference evapotranspiration (Eto) of 6,2 mm/day and crop coeffcients (Kc) based on FAO-56. The simulation results demonstrated that an 80 m3 storage tank could sufficiently meet irrigation demands for approximately 120 days during the dry season, aligning with the major growth cycles of horticultural crops in the study area. These findings highlight that an optimally designed RWH system integrated with drip irrigation can enhance agricultural resilience in dry tropical regions and provide an applicable solution for farmers to mitigate crop failure risk due to drought.